Environmental Engineering, Innovations, and Management. Editorial Review - Kuzmin, Andrey; Pinchuk, Valeriya A. (Begell House Inc., USA, 2023)
ENG: In recent years, special attention has been paid to environmental safety in various fields of application. Among all human activities, applications related to energy are always in high demand. At the same time, many of them affect climate change and can lead to biodiversity degradation and other environmental problems. The International Journal of Energy for a Clean Environment is a periodical that publishes high-quality research on the intersection of energy and the environment. The current issue of the journal presents the results obtained by researchers from different countries and different fields of research, devoted to some points in the field of energy and environmental management.
A. Kuzmin: ORCID 0000-0003-4091-4416; V. Pinchuk: ORCID 0000-0001-7684-1867
Keywords: energy efficiency; coefficient of performance; environmental protection; low emission combustion; power engineering; hydrogen engineering; КЕСЕ; TECHNOLOGY::Other technology::Environmental engineering